On the feasibility of Moodle use to assist deaf and hard of hearing Grade 9 learners with mathematics problem-solving - Damon, Nolan Brandon (Stellenbosch : Stellenbosch University, 2015)
ENGLISH ABSTRACT: This thesis sets out to examine Moodle use to assist Deaf and Hard of Hearing Grade 9 learners with understanding mathematics problem-solving. The methodology used in this research project is that of formative evaluation. In this qualitative data analysis I worked as a participant-observer with three Deaf and H/H Grade 9 learners from a local school for the Deaf and H/H. These learners engaged in a course constructed in Moodle based on ratio and rate. The course was designed along the lines of a constructivist pedagogical model, different levels of learning as well as including multi representational features. Through the qualitative analysis of the interviews conducted with learners who participated in the research project and observation done by the teacher researcher, three categories emerged i.e. Weaknesses, Potential strengths and Learner suggestions. Although the findings indicate that different factors negatively impact Deaf and H/H learners’ ability to solve mathematics problems, it also highlights the representational features of mathematics content via Moodle, and how it can assist Deaf and H/H learners with the struggle with mathematics problem-solving.